ANALYSIS OF SPORT INITIATION TO BASKETBALL WITHIN A SPORTS CLUB AND TWO PRIVATE SCHOOLS (Fiep Bulletin - online, 2013)
The objective of the research was identifying and analyzing the predominant methodology and practices used in the process of sport education, specifically in the teaching of basketball. The methodology used had a qualitative, descriptive and explanatory character. The instrument for data collection was in-class filming. The subjects of research were students and teachers from sport initiation schools (specifically basketball lessons) within two private elementary and high schools, and a sports club in the cities of Vitoria and Vila Velha. The study results showed that the teachers from these institutions tend to prefer the analytical-synthetic methodology and not consider the education requirements which include technical, tactical and coordination abilities.
Keywords: Methodology; Basketball; Sport initiation.